2017
DOI: 10.21448/ijsm.323800
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Volatile Oil Composition, Phenolics and Antioxidant Activity of Bay (Laurus nobilis) Leaf and Usage in Cosmetic Applications

Abstract: In this study, the components of the volatile oil obtained from Laurus nobilis leaves by steam distillation were determined using Agilent 6890 Gas Chromatography (GC) -5975 Mass Spectrometry (MS). The antioxidant activities of different extracts of L. nobilis leaves were determined by using DPPH • (2,2-diphenyl-1picrylhydrazyl) free radical scavenging activity, β-carotene-linoleic acid bleaching assay and ABTS •+ (2,2'-azinobis(3-ethylbenzothiazoline-6-sulphonic acid) cation radical decolorization assay. Deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 37 publications
4
11
0
1
Order By: Relevance
“…(2017) tested mandarin peels with different extraction methods and extraction solvents, and achieved the highest yield Kivrak et al (2017) have found that ethanolic extract of L. nobilis possess higher TFC than water extract, which is similar to our results, with noticeable higher TFC in methanolic extracts. Likewise, the ethanolic extract of bay leaves from Morocco had the highest TFC (Taroq et al, 2018).…”
Section: Yields Total Phenolic and Flavonoid Contents Of Extractssupporting
confidence: 82%
See 3 more Smart Citations
“…(2017) tested mandarin peels with different extraction methods and extraction solvents, and achieved the highest yield Kivrak et al (2017) have found that ethanolic extract of L. nobilis possess higher TFC than water extract, which is similar to our results, with noticeable higher TFC in methanolic extracts. Likewise, the ethanolic extract of bay leaves from Morocco had the highest TFC (Taroq et al, 2018).…”
Section: Yields Total Phenolic and Flavonoid Contents Of Extractssupporting
confidence: 82%
“…obtained different amounts of TPC in the study of ethanolic extracts of leaves and stems of basil collected from different locations in Egypt and concluded that this difference may be due to various climatic, seasonal and geographical conditions of the locations. Such dissimilarities can be also noticed in our results among samples of different origin Kivrak et al (2017). analyzed four L. nobilis leaves extracts and found higher TPC in ethanolic extract compared to water extract.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…Uçucu yağ eldesinde en sık değerlendirilen bitkiler arasında lavanta, fesleğen, karanfil, biberiye, defne ve tarçın yer almaktadır. Laurus nobilis (Akdeniz defnesi) güney Akdeniz sahasına özgü, yüksekliği 8-10 m'ye erişebilen, sürekli yeşil kalan ağaçsı bir çalı olup, yaprak ve meyveleri uçucu yağ eldesinde kullanılabilmektedir [10][11]. Yapraklarındaki uçucu yağ içeriği %1-3 aralığındadır ve ana bileşeni 1,8-cineole'dur.…”
Section: Introductionunclassified